Start‐ups and entrepreneurial teams. (29th September 2021) - Yang, Hong; Cozzarin, Brian Paul; Peng, Can; Xu, Chun
Abstract : We survey 398 Chinese entrepreneurs within 118 entrepreneurial teams to investigate external social capital's impact on: the decision to start a venture and the mediating role that risk perception plays in that decision. Our results confirm that external social capital has a significant and positive effect on the decision to start a venture, while risk perception partly mediates this relationship. Furthermore, we find that the three dimensions of external social capital drive the decision to start a venture differently. The most important domains of external social capital are commercial social capital, followed by technical social capital and institutional social capital.